Exploring the discrete tools used by laminators in composites manufacturing: application of novel concept. (2nd October 2015) - Jones, H.V.; Chatzimichali, A.P.; Middleton, R.; Potter, K.D.; Ward, C.
Abstract: This research investigates the handheld and often personally owned tools used by laminators to form advanced composites into components for aerospace, defense, and autosport; and reports on the application of a novel concept. The lack of formal knowledge that surrounds the existence and use of these tools presents an opportunity to explore what significance they have for process standardization and composites' design and manufacture. The paper presents results from layup trials that were performed to test a prototyped tool, designed with user-centered and geometry-driven research in mind. The trials showed tool use is aligned with the laminator's goals for the layup task; and suggest that it is also used as the laminator's method for reporting quality feedback. The trials also raised questions about why the laminators habitually use their tools and the necessity of supporting a laminator through the decision processes involved in a layup task. This suggests the development of a prototyped tool can be of significant benefit in the realm of skills and training. Graphical abstract: